Deconstruction and Genealogy of Latin American Good Living (Buen Vivir). The (Triune) Good Living and its Diverse Intellectual Wellsprings - Antonio Luis Hidalgo-Capitán; Ana Patricia Cubillo-Guevara (Revue Internationale de Politique de Développement)
The purpose of this chapter is to identify the different meanings of Latin American Good Living (buen vivir) and its diverse intellectual wellsprings, with a focus on the political economy of development. The authors try to answer the following questions: What different types of Good Living lie behind the overall concept? What intellectual wellsprings have the authors drunk from? The authors use the methodological strategies of deconstruction and conceptual genealogy, based on a broad bibliographic review. They conclude that three different types of Latin American Good Living exist: ‘indigenist’ and ‘pachamamist’, socialist and statist, and ‘ecologist’ and ‘post-developmentalist’. Moreover, they argue that synthesised notions of the concept exist. These versions are associated with different intellectual influences, such as sumak kawsay, suma qamaña and allin kawsay; the Andean world view; development with identity; the theory of reciprocity; post-development; liberation theology; dependency theory; the theory of ‘coloniality’; sustainable development; world-system theory; human development; endogenous development; eco-socialism; twenty-first century socialism; social justice; the economics of happiness; eudaemony; the economic theory of relational goods; the social and solidarity economy; intercultural feminism; the feminism of care; eco-feminism; the self-sufficient economy; community economy; barefoot economics and human scale development theory; the Buddhist economy; ‘post-extractivism’; ‘de-growth’; deep ecology and the theory of conviviality.